Study of Flow Characteristics in a Closed-Loop Low-Speed Wind Tunnel - Ahmad Anis; Sutardi Sutardi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2017)
Wind tunnel is an element or experimental device that plays an important role in the development of aerodynamics. In general, there are two types of wind tunnels: open-loop wind tunnels and closed-loop wind tunnels. Furthermore, based on the flow velocity in the wind tunnel, the wind tunnel can also be categorized into several types: low-speed wind tunnel and high-speed wind tunnel, including sub-sonic and supersonic wind tunnels. In this study it is used a low-speed closed-loop wind tunnel type. The maximum atainable velocity of airflow in the wind tunnel is about 46 m/s with turbulence intensity (TI) as low as 0.41 percent. The flow parameters that being evaluated in this study include the velocity profiles and intensity of turbulence (TI) in some parts or sections of the wind tunnel. Pressure measurements in the wind tunnel are performed using a Pitot tube connected to a calibrated pressure transducer. The measured values of pressures are then converted into the fluid velocities and turbulence intensities. The results show that the flow quality in the main test section of the wind tunnel is good enough. The intensity of the flow turbulence on the inlet side of the test section is about 0.41 percent at the centerline velocity of approximately 40 m/s. In some parts of the wind tunnel, turbulence intensity is still relatively high, as in the small elbow outlet where TI is higher than 18 percent.